The Effectiveness of Durante Hemodialysis Packed Red Cells (PRC) Transfusion on Hemoglobin Levels - Pria Wahyu Romadhon Girianto; Mega Wahyu Mulyasari (STIKes Patria Husada Blitar, 2021)
Renal Disease was a chronic disease that the most attacking people in Indonesia. Damage to this vital organ in the human body greatly affected a person's health condition, one of which was anemia. This study aimed to determine the effectiveness of Durante hemodialysis PRC transfusions on hemoglobin levels. The method used was Pre-experimental design, with the One group pre-post test design approach. With a sample of 49 patients who underwent regular hemodialysis at RSUD dr. Iskak Tulungagung. Data were obtained by direct observation. Processed by computerized methods with a statistical t-test, the significance level (Î±) was 0.05. The study results showed that the hemoglobin levels of the pre-Durante hemodialysis PRC transfusion patients were 4-5 mg/dl (53.06%), and the hemoglobin levels of the post-Durante hemodialysis PRC transfusion patients were 6.1-7 mg/dl (34.69%). The results of statistical tests showed that there was an increase in hemoglobin levels in patients who received Durante hemodialysis PRC transfusion by 1.22 mg/dl because p-value = 0.000 < 0.05 (Î±) means that there was an effect. It could be concluded that the delivery of Durante hemodialysis PRC transfusion could help increase hemoglobin levels. This finding was very helpful for chronic Renal Disease patients undergoing hemodialysis, who have been using erythropoietin preparations because PRC transfusions were cheaper and more effective when compared to using erythropoietin preparations